Endoscopic Retrograde Cholangiopancreatography in Patients with Choledochal Cyst, A Tertiary Care Experience - Erum Kazim, Muhammad Ali Taj, Aftab Ahmed Leghari, Rabia Feroz, Raheel Ahmed, Shahriyar Ghazanfar, (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: Our aim of this analysis was to evaluate the clinical features, laboratory values, radiological findings, endoscopic management, and technical success in patients with Choledochal cyst (CC). Materials & Methods: This retrospective study was carried out at our Endoscopy suite, between January 2010 to January 2022. All patients of choledochal cyst who underwent ERCPs in last 12 years were analyzed. Technical success was defined as achieving a biliary cannulation and successfully acquiring the desired goal. Descriptive and Frequency analysis were incorporated in Statistical analysis with SPSS. Results: Procedures performed in 100 patients with suspected choledochal cyst either for a diagnostic or therapeutic purpose were evaluated. 48 ERCPs (48%) were performed for therapeutic purpose and 52 (52%) for diagnostic purpose. Diagnostic findings after successful ERCP were CC in 67 (67%), CC with stone in 28 (28%), CC with cholangiocarcinoma in four (4%) and CC with biliary stricture in one (1%). No mortality was documented in our patients who underwent Procedure. Patients referred for surgery were 92 (92%) and ERCP affected management in 100% (100/100 procedures). Practical Implications: This study will determine the clinical features, laboratory values, radiological findings, endoscopic management, and technical success in patients with Choledochal cyst. Conclusion: ERCP is a contemporary procedure, its utility in cases with CCs in a developing country with scarce resources and limited availability of gold standard modality (MRCP), is astounding and safe. Keywords: Endoscopic retrograde cholangiopancreatography; Choledochal cyst; Classification; Endoscopic management.